Information through remote sensing to reduce Lebanon's vulnerability to desertification - Khawlie M.; Faour G. (Environmental monitoring in the South-Eastern Mediterranean region using RS/GIS techniques, 2003)
Desertification is affecting Lebanon's environment and its resources, even though the country enjoys a fair amount of water and green cover. Many threats inducing land degradation are increasing the vulnerability of the country. The paper reveals those threats and emphasizes that facing them with proper solutions needs information. The more information, the less vulnerable is the country. Such information must be intersectorial, integrated and is best obtained through remote sensing, especially the use of indicators.